Assessment of climate change impacts and urban flood management schemes in central Shanghai. (November 2021) - Sun, Xiaojing; Li, Ruonan; Shan, Xinmeng; Xu, Hanqing; Wang, Jun
Abstract: Increasing urbanization combined with climate change has resulted in the increased risk of flooding in cities. Thus, assessing the effect of future climate change on urban flooding and adopting effective flood management measures is becoming increasingly important. In this study, an urban rainstorm model and a scenario simulation method were applied to central Shanghai, China. We first examined the risks of flooding in the study area under the impact of future climate change using a simulation with different rainfall return periods. We then evaluated the benefits of traditional drainage system adaptation measures and Low Impact Development (LID) practices on alleviating the current urban flood hazard. Finally, we explored the effectiveness of using an integrated flood management scheme to adapt to climate change. The results show that the urban flood volume increases non-linearly with increasing rainfall intensity under climate change. The maximum flooding area also increases accordingly, and is much more sensitive to smaller rainfall events. Both traditional drainage system adaptation measures and LID practices can effectively alleviate flooding, while an integrated flood management scheme that emphasizes the combination of the two methods is shown to be the most effective in reducing flooding under future climate change.